L’aménagement des bureaux et l’accueil du public - Jean-Marc Weller (La Nouvelle Revue du Travail)
The article looks at the different public reception systems that French Social Security offices have used throughout history. After inventorying background perspectives – which vary depending on whether sites are construed as locations, environments, spaces or frameworks – the author suggests exploring a succession of interfaces, including hygiaphones, counters, boxes and platforms. Questions at this level relate to the priorities being pursued through these different ways of interacting with the public, starting with modalities, stagings and impacts. The article goes on to pursue a precise socio-historic investigation demonstrating how a subtle consideration of working space might enhance understanding of the coherency but also contradictions associated with managerial action in this area.